Language choice and use among Malaysian legal professionals / Ain Nadzimah Abdullah - Ain Nadzimah, Abdullah (2008)
Theories which have been used in the study of language choice have anchored primarily on sociolinguistic approaches. These approaches are linked to Fishman’s (1972) concepts of who speaks what language to whom and when. Another group of theories draw upon the psychological factors to explain language choice. From the literature in this field of study, each approach has shown limitations in its use. The stand taken in this study is that sociolinguistic and psychological approaches can be combined into a single category of approaches that can theorize language choice. This study examines language choice through this combined interpretative framework to account for a more accurate explanation of language choice and use. A number of alternatives in environment allow investigation into language choice and use. In this study the legal workplace is identified as a significant and unique linguistic ecology where language choice is exercised. The legal domain is linked to the operations of justice which governs law and order. The National Language policy clearly dictates that Bahasa Malaysia be used in the administration of justice in the legal context. However, findings of the study suggest that pragmatics directs the language user in the legal workplace to exercise a language choice. Using an interpretative framework of combined approaches helped to explain language choice in this significant domain. The research approach employed in the study used three methods which are the questionnaire, interview and observation to gather data to elucidate the theory. Findings of the study also suggest that language plays an important role in the legal work domain in Malaysia not only because legal professionals regard mastery of both Bahasa Malaysia and English as critical languages for the performance of legal professional tasks but also because in a special sense there is the realization that language in the legal work domain can have enormous implications for the administration and dispensing of justice. Lastly, implications for the ii study indicate that language practices in the Malaysian courtroom are often contrary to Malaysian language policy.